Distribution of harumanis in Universiti Teknologi Mara Cawangan Perlis by using : goal programming model / 'Ain Syafiqah Abu Sofian - Abu Sofian, 'Ain Syafiqah (2019)
Harumanis is the fruit that can grow well in Perlis. Harumanis in Perlis is now get high demand in the market of Malaysia even to the international. As we know, the Harumanis trees planted at the field of UiTM Cawangan Perlis. Every year the staff was distributed the Harumanis to the locations that have demand but the problem is the demand cannot fulfill at all to the certain locations due to limiting factors. Harumanis also is the fruit very sensitive and easily got rotten. If the seller not sell in the short time it can rotten and waste. This study is undertaken to develop a goal programming model in order to investigate the distribution of Harumanis in UiTM Cawangan Perlis. Two objectives of this study are to maximize the total distribution of Harumanis at three different locations which are Perlis, Shah Alam and Malacca and to maximize the profit of Harumanis. POM-QM Windows software is used to build the model. Total distribution for Malacca and Shah Alam is achieved but in Perlis it not fully achieved and request for 671.95 kg to be fulfilled in Perlis. In general, the objectives of distribution of Harumanis has been achieved by UiTM Cawangan Perlis. This is due to all Harumanis have been sold out except the rejected. In conclusion, UiTM Cawangan Perlis need to increase the production of Harumanis in Perlis to ensure all the demands of Harumanis are fulfilled and get more profit in the future.